2022
DOI: 10.20525/ijrbs.v11i2.1662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of emancipatory pedagogy as a tool for democratic classrooms

Abstract: Sometimes, teachers or instructors find it challenging to understand or achieve a democratic education without compromising the quality pedagogical process. Hence, this study is conceptualised around the principles of emancipatory pedagogy as a tool to ensure effective classrooms democracy across levels of classrooms. This study answers the following question: how can emancipatory pedagogy be presented as an effective tool to implement a democratic classroom? This study locates its argument within a transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It also helps students build positive self-concepts, raise their level of engagement, and enhance their capacity to apply what they have learned in new contexts (Blinne, 2013;MacDougall, 2013;Mitchell et al, 2009;Sartor & Young Brown, 2004). It promotes a democratic and student-centred approach to learning, which is in line with the ongoing call for a more vibrant, democratic, and equal learning environment that is believed to improve student outcomes (Omodan, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…It also helps students build positive self-concepts, raise their level of engagement, and enhance their capacity to apply what they have learned in new contexts (Blinne, 2013;MacDougall, 2013;Mitchell et al, 2009;Sartor & Young Brown, 2004). It promotes a democratic and student-centred approach to learning, which is in line with the ongoing call for a more vibrant, democratic, and equal learning environment that is believed to improve student outcomes (Omodan, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…The authors suggest that transparent communication and inclusive decision-making processes are essential for building trust between university management and students and preventing conflicts. Similarly, studies have found that involving students in the decision-making process can help promote a sense of ownership and shared responsibility, reducing the likelihood of student protests (Nyambegera, 2018; Omodan & Ige, 2021). The authors argue that student involvement in decision-making can also help to improve academic outcomes and promote social cohesion on campus.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In democratic education, students have the right to express their views and feelings, question existing ideas and beliefs, and cooperate with other parties. Therefore, a democratic class is a learning process that encourages students to think for themselves and contribute to the decision-making process both in the classroom and in the school community [16].…”
Section: Learning Practices With An Egalitarian Pedagogy Approachmentioning
confidence: 99%